Comunidade brasileira em Berlim: análise dos processos identitários entre imigrantes - Batista, Roberta Rangel (2019)
The discussion about the identity phenomenon makes it possible to understand how individuals organize themselves based on the current social structure and their belonging to social groups. In this context, the migration process can be considered relevant to the study of social groups, since, it is possibly oriented by the mobility system belief and the status’ rise among the social categories. However, even believing in social mobility, the maintenance of a national community outside the country can be considered as an important network support aimed at sustaining the belonging to the national group of origin. As an example of this situation, Berlin, the capital of Germany, is notable for the number of Brazilians who live there and preserve the country's culture. Considering the definition of group and social belonging at the Social Identity Theory, this thesis aimed to analyze the identity processes among immigrants belonging to the Brazilian community in Berlin. To accomplish this task, three complementary studies were proposed: (E1) A first ethnographic study aimed the description about the social organization of the Brazilian community in Berlin, based on the discussion of its territorial, social and peers relationship dimensions. The data were treated by Categorical-Thematic Content Analysis; (E2) In a second study, it was intended to analyze the identity dimensions (cognitive, evaluative and affective) among the individuals belonging to the Brazilian community, based on their references to Brazilian and German groups. In this study, individual interviews with 100 immigrants living in the territory were carried out, based on a structured questionnaire. The questionnaire contained the PANAS feelings scale, the Psychosocial Values Questionnaire (QVP 24) and the word association technique to Brazilian and German terms. The data were treated by the Categorical Content Analysis, by the cluster analysis (using the SPAD-T software), by the Kruskal-Wallis, Mann-Whitney and chi-square tests (performed using the Statistical Package for the Social Sciences); Finally, a third study (E3) aimed to investigate and discuss the dynamics of belonging to Brazilian and German social groups, through the analysis of mental maps elaborated by Brazilian migrants’ children. Twelve children, aged between 6 and 12 years, participated in this last study. The data were treated by Categorical-Thematic Content Analysis. The results showed that the interviewed Brazilians invest in an organization of a community order, based on practices that rescue Brazilian culture in different dimensions, such as culture, politics, education, religiosity, gastronomy, music, friendship and Portuguese language within the group itself. The affective dimension shows itself as salient to the maintenance of belonging to the social group of origin, in a positive way, although the individuals recognize the different social positions status. The reaffirmation of the intergroup memory manifests itself in the mental maps elaborated by the immigrants’ children, who reproduce some of the strategies used by their parents to maintain a positive social self-image. It is argued that identity processes among Brazilian migrants in Berlin are experienced initially due to expectations generated through ideological representations governed by the flow of economic patterns. However, although the search for a more horizontal materialist situation in the German country, the Brazilians face distant, biased and cold social relations with the destination country group members’. Faced with this difficulty, and based on the need for social protection, the identity processes among individuals are strengthened in social creativity and in the sense of community. Their affective and cultural memories are resignified within the community practices, allowing the redefinition of social values, a modified status and a positive social identity.